Assessment of Southern Ocean water mass circulation and characteristics in CMIP5 models: Historical bias and forcing response. Issue 4 (9th April 2013) - Sallée, J.‐B.; Shuckburgh, E.; Bruneau, N.; Meijers, A. J. S.; Bracegirdle, T. J.; Wang, Z.; Roy, T.
Abstract : [1] The ability of the models contributing to the fifth Coupled Models Intercomparison Project (CMIP5) to represent the Southern Ocean hydrological properties and its overturning is investigated in a water mass framework. Models have a consistent warm and light bias spread over the entire water column. The greatest bias occurs in the ventilated layers, which are volumetrically dominated by mode and intermediate layers. The ventilated layers have been observed to have a strong fingerprint of climate change and to impact climate by sequestrating a significant amount of heat and carbon dioxide. The mode water layer is poorly represented in the models and both mode and intermediate water have a significant fresh bias. Under increased radiative forcing, models simulate a warming and lightening of the entire water column, which is again greatest in the ventilated layers, highlighting the importance of these layers for propagating the climate signal into the deep ocean. While the intensity of the water mass overturning is relatively consistent between models, when compared to observation‐based reconstructions, they exhibit a slightly larger rate of overturning at shallow to intermediate depths, and a slower rate of overturning deeper in the water column. Under increased radiative forcing, atmospheric fluxes increase the rate of simulated upper cell overturning, but this increase is counterbalanced by diapycnal fluxes, including mixed‐layer horizontal mixing, and mostly vanishes. Key Points: Models have a consistent warm and light bias spread over the entire water column Small warm bias is associated with climate important errors in sea‐ice extent While air‐sea fluxes increase its rate, overturning change is small in the future